Geoscience of Climate and Energy 13. The Environmental Hydrogeology of the Oil Sands, Lower Athabasca Area, Alberta - Miall, Andrew D. (Geoscience Canada, 2013)
Shallow fresh groundwater and deep saline groundwater are used together with surface water in the extraction of bitumen from the Athabasca Oil Sands both in the surface mining and in situ operations. However, increasing efficiencies in processing technologies have reduced water use substantially and currently at least 75% of the water used in most operations is recycled water. Much concern has been expressed regarding contamination of surface waters by seepage from tailings ponds, but hydrogeological studies indicate that this is not happening; that seepage capture design is effective. Oil sands mining and in situ project licensing and operation regulations include Environmental Impact Assessments that mandate considerable hydrogeological measurement and monitoring work. However, little of this is independently evaluated for accuracy or synthesized and interpreted for the public. Recent changes in Alberta environmental regulation, including the establishment of the Alberta Environmental Monitoring Management Board (in October 2012) are expected to bring new transparency to environmental management of Oil Sands operations. SOMMAIRE On utilise conjointement des eaux douce de faibles profondeur, des eaux souterraines salines profondes avec des eaux de surface dans l’extraction du bitume des sables bitumineux de l’Athabasca, tant dans le procédé d’extraction in situ qu’en surface. Par ailleurs, l’accroissement de l’efficacité des technologies de traitement a considérablement réduit la consommation d’eau et, à l’heure actuelle, au moins 75% de l’eau utilisée dans la majorité des opérations est de l’eau recyclée. Beaucoup d’inquiétude a été exprimée concernant la contamination des eaux de surface par la percolation des eaux des bassins de décantation des résidus, mais des études hydrogéologiques indiquent que ce n’est pas le cas, et que le concept de capture des infiltrations est efficace. L’octroi de permis d’exploitation ainsi que les procédés d’exploitation des sables bitumineux, par extraction en surface ou in situ, comportent des évaluations d’impact sur les milieux de vie, est assorti de mandats élaborés de mesures hydrologiques et de suivi. Cela dit, peu de ces mesures sont évaluées de manière indépendante quant à leur exactitude, leur mise en forme et leur interprétation pour le grand public. Les changements récents dans la réglementation environnementale en Alberta, y compris la mise en place du Alberta Environmental Monitoring Management Board (en Octobre 2012) devraient aboutir à une nouvelle transparence de la gestion environnementale de l’exploitation des sables bitumineux. DOI: http://dx.doi.org/10.12789/geocanj.2013.40.016